Pyknon-Containing Transcripts Are Downregulated in Colorectal Cancer Tumors, and Loss of PYK44 Is Associated With Worse Patient Outcome - Evangelista, Adriane Feijó; de Menezes, Weder Pereira; Berardinelli, Gustavo Noriz; Dos Santos, Wellington; Scapulatempo-Neto, Cristovam; Guimarães, Denise Peixoto; Calin, George A.; Reis, Rui Manuel (Frontiers in Genetics, 2020)
Pyknons are specific human/primate-specific DNA motifs at least 16 nucleotides long, repeated in blocks in intergenic and intronic regions of the genome, and can be located in a new class of non-coding RNAs of variable length. Recent studies reported that pyknon deregulation could be involved in the carcinogenesis process, including colorectal cancer. We evaluated the expression profile of a set of 12 pyknons in 73 molecularly characterized colorectal cancer (CRC) patients. The pyknons (PYK10, PYK14, PYK17, PYK26, PYK27, PYK40, PYK41, PYK42, PYK43, PYK44, PYK83, and PYK90) expression was determined by qRT-PCR. A pilot analysis of twenty cases was performed, and consistent results were obtained for PYK10, PYK17, PYK42, PYK44, and PYK83. Further, the expression of the selected pyknons was evaluated in 73 CRC cases. Moreover, in 52 patients, we compared the expression profile in both tumor and normal tissues. All five pyknons analyzed showed significantly lower expression levels in the tumor compared to normal tissue. It was observed an association between expression of PYK10 with TP53 mutations (p=0.029), PYK17 to histologic grade (p=0.035), and PYK44 to clinical staging (p=0.016). Moreover, levels of PYK44 were significantly associated with the patient's poor overall survival (p=0.04). We reported the significant downregulation of pyknons motifs in tumor tissue compared with the normal counterpart, and the association of PYK44 lower expression with worse patient outcome. Further studies are needed to extend and validate these findings and determine the clinical-pathological impact.